Aproximación a la historiografía sobre artesanos, trabajadores de las haciendas y obreros en el Estado de México - Pedrero Nieto, Gloria; Lagunas Ruiz, Hilda; Reynoso Jaime, Jenaro (La Colmena; Núm. 58 (2008), 2017)
-